Baseline IL-6 is a biomarker for unfavourable tuberculosis treatment outcomes: a multisite discovery and validation study. Issue 4 (21st April 2022) - Gupte, Akshay N.; Kumar, Pavan; Araújo-Pereira, Mariana; Kulkarni, Vandana; Paradkar, Mandar; Pradhan, Neeta; Menon, Pradeep; Padmapriyadarsini, Chandrasekaran; Hanna, Luke-Elizabeth; Yogendra Shivakumar, Shri Vijay Bala; Rockwood, Neesha; Du Bruyn, Elsa; et al.
Background: Biomarkers of unfavourable tuberculosis (TB) treatment outcomes are needed to accelerate new drug and regimen development. Whether plasma cytokine levels can predict unfavourable TB treatment outcomes is unclear. Methods: We identified and internally validated the association between 20 a priori selected plasma inflammatory markers and unfavourable treatment outcomes of failure, recurrence and all-cause mortality among adults with drug-sensitive pulmonary TB in India. We externally validated these findings in two independent cohorts of predominantly diabetic and HIV co-infected TB patients in India and South Africa, respectively. Results: Pre-treatment interferon-γ, interleukin (IL)-13 and IL-6 were associated with treatment failure in the discovery analysis. Internal validation confirmed higher pre-treatment IL-6 concentrations among failure cases compared with controls. External validation among predominantly diabetic TB patients found an association between pre-treatment IL-6 concentrations and subsequent recurrence and death. Similarly, external validation among predominantly HIV co-infected TB patients found an association between pre-treatment IL-6 concentrations and subsequent treatment failure and death. In a pooled analysis of 363 TB cases from the Indian and South African validation cohorts, high pre-treatment IL-6 concentrations were associated with higher risk of failure (adjusted OR (aOR) 2.16, 95% CI 1.08–4.33; p=0.02), recurrence (aOR 5.36, 95% CI 2.48–11.57; p<0.001) and death (aOR 4.62, 95% CI 1.95–10.95; p<0.001). Adding baseline IL-6 to a risk prediction model comprised of low body mass index, high smear grade and cavitation improved model performance by 15% (C-statistic 0.66 versus 0.76; p=0.02). Conclusions: Pre-treatment IL-6 is a biomarker for unfavourable TB treatment outcomes. Future studies should identify optimal IL-6 concentrations for point-of-care risk prediction. Pre-treatment IL-6 is a biomarker for unfavourable tuberculosis treatment outcomes independent of disease severity and improves the performance of risk prediction models comprised of established clinical predictors https://bit.ly/38394xE